Quantitative trait loci associated with resistance to a potato isolate of Verticillium albo‐atrum in Medicago truncatula. (19th July 2013) - Negahi, A.; Ben, C.; Gentzbittel, L.; Maury, P.; Nabipour, A. R.; Ebrahimi, A.; Sarrafi, A.; Rickauer, M.
<x xml:space="preserve">Abstract</x> Verticillium albo‐atrum is responsible for considerable yield losses in many economically important crops, among them alfalfa (Medicago sativa). Using Medicago truncatula as a model for studying resistance and susceptibility to V. albo‐atrum, previous work has identified genetic variability and major resistance quantitative trait loci (QTLs) to Verticillium. In order to study the genetic control of resistance to a non‐legume isolate of this pathogen, a population of recombinant inbred lines (RILs) from a cross between resistant line F83005.5 and susceptible line A17 was inoculated with a potato isolate of V. albo‐atrum, LPP0323. High genetic variability and transgressive segregation for resistance to LPP0323 were observed among RILs. Heritabilites were found to be 0·63 for area under the disease progress curve (AUDPC) and 0·93 for maximum symptom score (MSS). A set of four QTLs associated with resistance towards LPP0323 was detected for the parameters MSS and AUDPC. The phenotypic variance explained by each QTL (R2) was moderate, ranging from 4 to 21%. Additive gene effects showed that favourable alleles for resistance all came from the resistant parent. The four QTLs are distinct from those described for an alfalfa V. albo‐atrum isolate, confirming the existence of several resistance mechanisms in this species. None of the QTLs co‐localized with regions involved in resistance against other pathogens in M. truncatula.